Modeling an Optimal 3D Skin-on-Chip within Microfluidic Devices for Pharmacological Studies - Estibaliz Fernandez-Carro; Maricke Angenent; Tamara Gracia-Cazaña; Yolanda Gilaberte; Clara Alcaine; Jesús Ciriza (MDPI AG, 2022)
Preclinical research remains hampered by an inadequate representation of human tissue environments which results in inaccurate predictions of a drug candidate's effects and target's suitability. While human 2D and 3D cell cultures and organoids have been extensively improved to mimic the precise structure and function of human tissues, major challenges persist since only few of these models adequately represent the complexity of human tissues. The development of skin-on-chip technology has allowed the transition from static 3D cultures to dynamic 3D cultures resembling human physiology. The integration of vasculature, immune system, or the resident microbiome in the next generation of SoC, with continuous detection of changes in metabolism, would potentially overcome the current limitations, providing reliable and robust results and mimicking the complex human skin. This review aims to provide an overview of the biological skin constituents and mechanical requirements that should be incorporated in a human skin-on-chip, permitting pharmacological, toxicological, and cosmetic tests closer to reality.